BODY AND SOUL IN IBN SINA’S PHILOSOPHICAL SYSTEM: BETWEEN LOGIC, METAPHYSICS, AND NATURAL PHILOSOPHY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes Ibn Sīnā’s doctrine of body and soul within the framework of his philosophical system, which spans logic, metaphysics, and natural philosophy. It examines the logical structure of his arguments about the soul, the metaphysical distinction between essence and existence, and his view of the soul as an immaterial substance that employs the body as its instrument. Particular attention is given to how his natural philosophy and medical practice explain the interdependence of the bodily and spiritual dimensions and how this interdependence shapes the human path toward perfection.